Calculation of postenseness loss on table beams of central piers of General Rafael Urdaneta Bridge - Sarcos Portillo, Antonio; García Legl, Hildrun (Rev. Téc. Fac. Ing. Univ. Zulia)
A theoretical methodology is proposed to attempt an assessment of tension loss in the postensioned cables of the central pier table beams of General Rafael Urdaneta Bridge on Maracaibo Lake. This methodology 18 based on experimental tests run in situ. The importance of this methodology lies in the fact that the stays are joined to the table beam by concrete, making experimental measurement of tension impossible. The results indicate a possible 16% loss of their original tension. This procedure enables future evaluation of cable conditions.